The impact of differential pricing on perceived service quality and guest satisfaction: An empirical study of mid-scale hotels in India - Ansari, Amjad Imam; Singh, Amrik; Singh, Vipin (Turyzm/Tourism, 2023)
The aim of this article is to identify the key factors of differential pricing and its impact on perceived service quality and guest satisfaction. Great attention has been given by researchers to service quality and guest satisfaction in the tourism and hotel industry. This study however examines an integrated model of differential pricing, perceived service quality and guest satisfaction linked to value perception and satisfaction among guests for prices offered at the time of room booking, and the services available during their stay. A self-administered questionnaire was given to guests who stayed in mid-scale hotels and 334 responses were collected randomly. Structural equation modelling was used to examine the data set, a second-generation method that enables simultaneous modelling of a large number of independent and dependent variables. Partial least square SmartPLS 4.0 was used to evaluate the data. The measurement model and the structural model are the two used to examine the data. According to survey results and findings, booking channel and booking volume are significantly related to guest satisfaction. Additionally, the booking channel has a significant relationship with perceived service quality. Maintaining high-quality websites is crucial to attracting visitors and keeping them, eventually leading to more people using travel websites out of loyalty.